Successful surgical treatment of a gigantic congenital coronary artery fistula immediately after birth - Matsumoto, Yorihiko (Oxford University Press, 2012)
A foetus was prenatally diagnosed with a gigantic (12 mm) coronary artery fistula (CAF) from the left anterior descending (LAD) coronary artery to right ventricular apex at 38 weeks of gestation. LAD was dilated to 10 mm with partial aneurysmal changes. Because of concern for sudden ischaemic cardiogenic shock soon after birth, the child was electively delivered by caesarean section, with surgical fistula closure subsequently performed 1 h after birth. We also highly suspected the presence of a clinically significant accessory diagonal branch just around the fistula, thus direct fistula closure from outside the heart without cardiopulmonary bypass was abandoned and cardiopulmonary bypass was initiated. The terminal end of LAD was carefully opened, and the fistula was directly closed with four pairs of 6-0 polypropylene mattress sutures under cardioplegic arrest, while the opened terminal end of LAD was also repaired with plegetted 6-0 polypropylene mattress and over-and-over sutures. After 4 days of post-surgical extracorporeal life support for over-systemic pulmonary hypertension, the patient recovered without complications. Although postoperative echocardiography 5 months after the operation showed normal cardiac function without ventricular asynergy, the dilated and aneurysmal LAD remained unchanged.